FENOMENA PENCATATAN PERKAWINAN BAGI JANDA DI KUA KECAMATAN TANAH TUMBUH KABUPATEN TANJUNG JABUNG DITINJAU DARI HUKUM KELUARGA - Nindi Aliska Nasution (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This article aims to find out the process of registering marriages for widows in Tanah Grow District, Tanjung Jabung Regency. Uniquely, what is used instead of the divorce certificate for the prospective bride and groom is a certificate from the Village Head as a document requirement for carrying out the marriage. Meanwhile, Article 6 paragraph 2 letter (f) explains explicitly that the marriage registration procedure for widows is